Analisis Manfaat Pengembangan Organisasi di SD Negeri 17 Pakan Kurai di Kecamatan Guguak Panjang - Aldi (CV. ITTC INDONESIA, 2025)
This study aims to analyze the perspective of SDN 17 Pakan Kurai on the benefits of organizational development in improving the quality of education. The research used a qualitative descriptive approach with data collection techniques through interviews, observation, and document analysis. The findings reveal that organizational development has a positive impact on school management effectiveness, teacher job satisfaction, and the overall quality of learning. The study concludes that organizational development plays a key role in fostering adaptive, innovative, and quality-oriented educational institutions..